Cost analysis of a prospective multi-site cohort study of palliative care consultation teams for adults with advanced cancer: Where do cost-savings come from?. (April 2017) - May, Peter; Garrido, Melissa M; Cassel, J Brian; Kelley, Amy S; Meier, Diane E; Normand, Charles; Smith, Thomas J; Morrison, R Sean
Background: Studies report cost-savings from hospital-based palliative care consultation teams compared to usual care only, but drivers of observed differences are unclear. Aim: To analyse cost-differences associated with palliative care consultation teams using two research questions: (Q1) What is the association between early palliative care consultation team intervention, and intensity of services and length of stay, compared to usual care only? (Q2) What is the association between early palliative care consultation team intervention and day-to-day hospital costs, compared to a later intervention? Design: Prospective multi-site cohort study (2007–2011). Patients who received a consultation were placed in the intervention group, those who did not in the comparison group. Intervention group was stratified by timing, and groups were matched using propensity scores. Setting/participants: Adults admitted to three US hospitals with advanced cancer. Principle analytic sample contains 863 patients ( n UC  = 637; n PC EARLY  = 177; n PC LATE  = 49) discharged alive. Results: Cost-savings from early palliative care accrue due to both reduced length of stay and reduced intensity of treatment, with an estimated 63% of savings associated with shorter length of stay. A reduction in day-to-day costs is observable in the days immediately following initial consult but does not persist indefinitely. A comparison of early and late palliative care consultation team cost-effects shows negligible difference once the intervention is administered. Conclusion: Reduced length of stay is the biggest driver of cost-saving from early consultation for patients with advanced cancer. Patient- and family-centred discussions on goals of care and transition planning initiated by palliative care consultation teams may be at least as important in driving cost-savings as the reduction of unnecessary tests and pharmaceuticals identified by previous studies.